Parasympathetic Nerve Function Status in Major Depressive Disorder Patients and Its Correlation with Duration of Disease (Medicine Today, 2020)
Introduction:Cardiovascular (CV) morbidity is a major problem in patients suffering from depression. Greater CV mortality is found in cardiac patients with depression than without depression. Depressive disorder can cause altered autonomic nerve function. This study design to assess autonomic nerve function activity by heart rate variability analysis in patients with major depressive disorder and its correlation with duration of disease.Materials and Methods: This case study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka in 2011. 60 patients of both sexes with major depressive disorder (MDD) aged from 20-50 years were included in the study group (Group B). The patients were selected from out and inpatient Department of Psychiatry in Bangabandhu Sheik Mujib Medical University (BSMMU). Group B were divided into B-1 consisting of 30 drug naive MDD patients & B-2 consisting of 30 medicated MDD patients. For comparison age and sex matched 30 apparently healthy subjects (Group A) were also studied. The HRV parameters were recorded by 4 active channels, Polyrite-D machine. For statistical analysis ANOVA, independent sample t-test, chi-square test and Pearson’s correlation coefficient test were performed by using SPSS for windows version-16 as applicable.Results: Mean resting pulse rate, mean heart rate, systolic blood pressure were significantly higher in drug naive and medicated MDD patients in comparison with that of healthy control. Mean R-R interval, Max/Min R-R interval, SDNN, RMSSD, PNN50%, NN50% were significantly lower in this groups of patients. Correlation analysis showed negative correlations of SDNN, RMSSD, PNN50%, NN50% with disease duration which was statistically significant only for SDNN.Conclusion: Sympathovagal imbalance may occur in both drug naive and medicated MDD patients which is associated with higher sympathetic and lower vagal modulation of the heart rate. In addition, parasympathetic nerve function parameters show negative relationship with the duration of disease.Medicine Today 2020 Vol.32(2): 76-80